Religion and politics in Elizabethan England : The life of Sir Christopher Hatton - Younger, Neil (Book collections on Project MUSE., 2022)
This book provides a full account of the life and career of the Elizabethan politician and courtier Sir Christopher Hatton. A loyal favourite and minister of a Protestant queen, he was also a patron and protector of Catholics. This account of Hatton opens a new window into the complex religious politics of Elizabeth's reign.